Understanding Generation Z's Intentions To Apply For Jobs Through Employer Attractiveness, Corporate Reputation, and Social Media - Maulinda, Liestya Dwi; Aryati, Ana Sofia (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The fierce "war for talent" and the unique expectations of digital-native cohorts pose a significant challenge for corporate recruitment, creating an urgent need to understand the key drivers of job application intention. This study aims to analyze the influence of employer attractiveness, corporate reputation, and social media on the intention to apply for jobs among Generation Z. This study employs a quantitative approach with a causal research design. The population consists of 1,043 final-year students from the Faculty of Economics and Business, Universitas Brawijaya, with a sample of 104 respondents selected through a simple random sampling technique. Data were collected via a questionnaire and analyzed using multiple linear regression. The results indicate that employer attractiveness, corporate reputation, and social media each have a positive and significant influence on the intention to apply for a job, with social media emerging as the most dominant factor. The novelty of this research lies in its integrated model that confirms the primacy of digital channels in shaping the career decisions of Gen Z. The findings imply that companies must prioritize authentic social media strategies, while universities need to equip students with digital literacy skills for the modern job market.